2020
DOI: 10.1177/0267659120979564
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes and complications of bedside tracheostomy in the ICU for patients on ECMO

Abstract: Objective: Extracorporeal membrane oxygenation (ECMO) is increasingly employed in the management of patients with severe cardiac and pulmonary dysfunction. Patients commonly require tracheostomy for ventilator liberation. Though bedside percutaneous tracheostomy is commonly performed, it has the potential for increased complications, both surgical and with the ECMO circuit. We examined surgical outcomes of bedside percutaneous tracheostomy in the ECMO population. Methods: Patients were identified from an insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The safety of tracheostomy during ECMO support is another important issue. This study showed that the rate of tracheostomy-related local bleeding was approximately 30%, which is similar to previous reports (9,10,12). In addition, there was no signi cant difference in bleeding between the ET and DT groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The safety of tracheostomy during ECMO support is another important issue. This study showed that the rate of tracheostomy-related local bleeding was approximately 30%, which is similar to previous reports (9,10,12). In addition, there was no signi cant difference in bleeding between the ET and DT groups.…”
Section: Discussionsupporting
confidence: 92%
“…Less than 15% of the centers reported that they would perform a tracheostomy within one week after the onset of ECMO support(8). Although several single-center studies reported potential complications of tracheostomy during ECMO support, such as minor bleeding (with an incidence rate of approximately 10-30%), major bleeding (2-11%), pneumothorax (approximately 1.5%), ECMO circuit dysfunction (0 to 3.1%), and analgosedation-related hypotension (less than 1%) (9)(10)(11), a recent international multicenter retrospective study conducted over a 9-year period and including 1,168 severe ARDS patients treated with ECMO reported that major complications were uncommon and that the rate of minor complications was acceptable (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent retrospective studies reported that tracheostomy can be safely performed in selected ECMO patients in whom benefits outweigh the risks, without an associated increase of transfusions and with a consequent reduction in analgesic, inotropic, and vasopressor usage. 61,62 Larger prospective studies need to confirm these promising results. Finally, we consider ECMO weaning, which may be either before or after weaning from mechanical ventilation, depending on the preference and experience of the team as well as the clinical scenario.…”
Section: Mechanical Ventilation During Ecmo Introductionmentioning
confidence: 99%
“…However, recent retrospective studies reported that tracheostomy can be safely performed in selected ECMO patients in whom benefits outweigh the risks, without an associated increase of transfusions and with a consequent reduction in analgesic, inotropic, and vasopressor usage. 61 62 Larger prospective studies need to confirm these promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who require V-V ECMO routinely need tracheostomy; these are the sickest patients and require tracheostomy early and systematically [ 8 , 9 , 10 , 11 ]. Turning the ventilator to ‘standby’ mode and allowing decompression of the breathing circuit might lead to de-recruitment and desaturation, but aerosolization is minimized.…”
Section: Introductionmentioning
confidence: 99%